Protocol for a Multistage Mixed-Methods Evaluation of Multidisciplinary Chronic Kidney Disease Care Quality Following Integration of Virtual and In-Person Care During the COVID-19 Pandemic. (June 2022) - Bevilacqua, Micheli; Chiu, Helen; Melnyk, Yuriy; Williams, Janet; Chohan, Robin; Wei, Julie; Stoll, Dominik; Fryer, Michele; McGuire, Marlee; Logie, Anne; Watson, Paul; Levin, Adeera
Background: Multidisciplinary care of patients with chronic kidney disease (CKD) as it previously existed was predicated on an evidence and experience base of improved patient outcomes within an established and well-described service delivery model. The onset of the COVID-19 pandemic brought with it a departure from this established care delivery model toward integration of virtual care and in-person care. Objective: To develop an evaluation framework to determine whether this shift in service delivery models has affected quality of multidisciplinary kidney care and/or patient-clinician interactions and relationships. Design: A sequential multiphase, mixed-methods evaluation. Setting: All 15 British Columbia (BC) multidisciplinary kidney care clinics (KCCs). Participants: All patients and all clinicians in all KCCs across BC will be invited to participate in the planned evaluation. Measurements: Qualitative and quantitative feedback from patients and families living with CKD and KCC clinicians. Methods: The planned multiphase evaluation of virtual care integration in KCCs will be conducted across all 15 KCCs in the province of BC, Canada. The following phases are proposed: (1) review of current virtual care integration and practices, (2) assessment of patient and clinician experiences and perspectives via semi-structured interviews, (3) validation of those patient and clinician perspectives via survey of a larger sample, (4) compilation and analysis of all phases to provide informed recommendations for patient and visit format selection in a mixed in-person and virtual multidisciplinary clinic setting. Limitations: This work will not capture any information about the relationship between differences in virtual usage parameters and clinical outcomes or financial implications. Conclusions: There is no existing framework for either evaluation of multidisciplinary CKD care quality in a virtual setting or evaluation of care quality following a substantial change in service delivery models. The proposed evaluation protocol will enable better understanding of the nuances in kidney care delivery in this new format and inform how best to optimize the integration of virtual and pre-existing formats into kidney clinic care delivery beyond the pandemic. Beyond the current evaluation, this protocol may be of use for other jurisdictions to evaluate their own local instances of virtual care implementation and integration. The model may be adapted to evaluate quality of multidisciplinary kidney care delivery following other changes to clinic service delivery models.